2010
DOI: 10.1111/j.1758-2229.2010.00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation in Azospirillum brasilense exposed to starvation

Abstract: Bacteria have developed mechanisms that allow them maintaining cell viability during starvation and resuming growth when nutrients become available. Among these mechanisms are adaptive mutations and phase variation, which are often associated with DNA rearrangements. Azospirillum brasilense is a Gram-negative, nitrogen-fixing, plant growth-promoting rhizobacterium. Here we report phenotypic variants of A. brasilense that were collected after exposure to prolonged starvation or after re-isolation from maize roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 54 publications
1
23
0
1
Order By: Relevance
“…Phenotypic variation is often associated with large DNA rearrangements and PVs can be distinguished from their parental strains by diverse DNA fingerprinting methods [13,3941]. Here we showed that 7a1 PVs slightly differed from the parental strain in their PFGE profile following restriction with XbaI and variant 7a1V2 slightly differed from the parental strain (and from variant 7a1V1) in REP-PCR.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Phenotypic variation is often associated with large DNA rearrangements and PVs can be distinguished from their parental strains by diverse DNA fingerprinting methods [13,3941]. Here we showed that 7a1 PVs slightly differed from the parental strain in their PFGE profile following restriction with XbaI and variant 7a1V2 slightly differed from the parental strain (and from variant 7a1V1) in REP-PCR.…”
Section: Discussionmentioning
confidence: 57%
“…In such cases, PVs can be distinguished from their parental strains by DNA fingerprinting methods [13,3941]. We assessed whether variants M6V1 and M6V2 as well as 7a1V1 and 7a1V2 differ from their corresponding parental strains, in pulse field gel electrophoresis (PFGE) and repetitive-PCR (rep-PCR) profiles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various DNA regulatory mechanisms are involved in phenotypic variation: site specific inversion, recombinational deletion, transposition, spontaneous duplication and mutation, slipped-strand mispairing, genomic rearrangement, and differential methylation. Phenotypic variation affects root colonization, biocontrol activity, aggregation, exopolysaccharide production, lipopolysaccharide production, exoenzyme production, and secondary metabolite production (Katupitiya et al, 1995;van den Broek et al, 2005;Vial et al, 2006;Wisniewski-Dyé & Vial, 2008;Lerner et al, 2010). In addition, according to van der Woude & Baumler (2004), changes in global regulatory protein expression can lead to an alteration in the expression of several operons, thus resulting in phenotypic variation.…”
Section: Introductionmentioning
confidence: 99%